Analysing the implications of hospitality and culinary educators' tacit knowledge utilization / Michael Anastasiou - Anastasiou, Michael (Faculty of Hotel & Tourism Management, 2019)
The current study examines the workplace issues that affect hospitality and culinary arts educators (HCAEs) in fully utilising personal tacit knowledge gained from their working experience in the industry in a vocational education setting. The purpose of this qualitative case study was to investigate the factors impeding HCAEs' tacit knowledge utilisation and determine their consequences on the teaching and learning process. Sixty-two HCAEs were interviewed face-to-face. Through the data analysis, four significant factors were identified that affect tacit knowledge utilisation within a vocational educational institution. These factors are related to forces that affect HCAEs at an individual level, and they are divided into four categories: (a) knowledge issues, (b) employment issues, (c) training and learning issues, and (d) organisational issues. The consequences have a serious impact on the innovation process in teaching and learning, while opportunities to capitalise on the knowledge exchange process are lost. The lack of a learning organisational culture and ineffective organisational structures in relation to operating standards results in HCAEs being unable to effectively stimulate their students' absorptive capacity. Thus, the learnby-doing approach to support the learning outcomes of a course and improve the professional/vocational aspects of the program focuses only on the dry teaching dimension and the assigned curriculum.